ANDROID-BASED LEARNING MEDIA DEVELOPMENT FOR CHAPTER 2D AND 3D ANIMATION - Rahman, Yudi; Irsyadunas, Irsyadunas; Darman, Regina Ade (Universitas PGRI Sumatera Barat, 2021)
The Students of 2D and 3D Animation subjects class XI Multimedia SMK Negeri 1 Sijunjung have difficulty in understanding learning materials. Absence of learning media that support learners' learning outcomes in 2D and 3D Animation subjects makes it difficult for learners to understand the subject matter. This research aims to develop a valid and practical android-based learning medium on the subjects of 2D and 3D Animation. The research method used Research and Development (R&D) with ADDIE (Analyze-Design-Development-Implement-Evaluate) model. The results of the study are: (1) media validation results obtained with an average of 0.77 with the category